Advances in practical applications of cyber-physical multi-agent systems : the PAAMS collection : 15th International Conference, PAAMS 2017, Porto, Portugal, June 21-23, 2017, Proceedings /: the PAAMS collection : 15th International Conference, PAAMS 2017, Porto, Portugal, June 21-23, 2017, Proceedings. (2017) - Unknown
No abstract available